2015
DOI: 10.1111/tbed.12401
|View full text |Cite
|
Sign up to set email alerts
|

Dromedary Camels and the Transmission of Middle East Respiratory Syndrome Coronavirus (MERS-CoV)

Abstract: Middle East respiratory syndrome coronavirus (MERS-CoV) is an existential threat to global public health. The virus has been repeatedly detected in dromedary camels (Camelus dromedarius). Adult animals in many countries in the Middle East as well as in North and East Africa showed high (>90%) sero-prevalence to the virus. MERS-CoV isolated from dromedaries is genetically and phenotypically similar to viruses from humans. We summarise current understanding of the ecology of MERS-CoV in animals and transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(124 citation statements)
references
References 52 publications
3
119
0
Order By: Relevance
“…In addition, young camels have been more acutely infected in past studies and may have died rather than seroconverted [18]. Similar studies elsewhere also indicated a higher seroprevalence in adult than in juvenile camels [30]. Although the number of seropositive samples was comparable in female and male camels, the number of confirmed PCR positive MERS-CoV animals was significantly higher in females than males (p < 0.05).…”
Section: Discussionmentioning
confidence: 67%
“…In addition, young camels have been more acutely infected in past studies and may have died rather than seroconverted [18]. Similar studies elsewhere also indicated a higher seroprevalence in adult than in juvenile camels [30]. Although the number of seropositive samples was comparable in female and male camels, the number of confirmed PCR positive MERS-CoV animals was significantly higher in females than males (p < 0.05).…”
Section: Discussionmentioning
confidence: 67%
“…40 Furthermore, the practice of dromedary camel husbandry is regarded as a vital aspect of the nomadic lifestyle culture in the GCC region, where camels are used as a source of food, folk remedies, garments, transport, trade, and for racing, a multi-million dollar industry. 41 All the aforementioned findings strengthen the belief in the socio-cultural model, which emphasizes that social and cultural variables inexorably interact with biology to affect the health of human beings.…”
Section: The Environmentsupporting
confidence: 59%
“…Improved surveillance of camels along camel trade routes, camel herds in Dhaka, and persons who have close contact with camels will help assess the transboundary movement and the risk for zoonotic transmission in Bangladesh. Given the ubiquity of MERS-CoV in dromedary camels, the predictable seasonal movement of camels into Dhaka, and a higher incidence of infection in persons with frequent contact with camels ( 10 ), targeted public health messaging that promotes handwashing after contact with camels and avoidance of exposure to camel excreta might help reduce the risk for zoonotic MERS-CoV transmission.…”
mentioning
confidence: 99%